The role of the cervix in fertility: is it time for a reappraisal? - Martyn, F; McAuliffe, F M; Wingfield, M (Human reproduction (Oxford), 2014)
Knowledge regarding the role of the cervix in fertility has expanded considerably over the past 20 years and in this article, we propose that it is now time for its function to be reappraised. First, we review the anatomy of the cervix and the vaginal ecosystem that it inhabits. Then, we examine the physiology and the role of the cervical mucus. The ongoing mystery of the exact mechanism of the sperm-cervical mucus interaction is reviewed and the key players that may unlock this mystery in the future are discussed. The soluble and cellular biomarkers of the lower female genital tract which are slowly being defined by contemporary research are reviewed. Attempts to standardize these markers, in this milieu, are hindered by the changes that may be attributed to endogenous or exogenous factors such as: age, hormonal changes during the menstrual cycle, ectropion, infection, smoking and exposure to semen during sexual intercourse. We review what is known about the immunology of the cervix. With the widespread use of large loop excision of the transformation zone (LLETZ) for treatment of cervical intraepithelial neoplasia, the anatomy of the cervix is changing for many women. While LLETZ surgery has had very positive effects in the fight against cervical cancer, we debate the impact it could have on a woman's fertility.